Communication and Collaboration Among Heterogeneous Unmanned Systems Using SAE JAUS Standard Formats and Protocols. Issue 5 (2015) - Incze, Michael L.; Sideleau, Scott R.; Gagner, Chris; Pippin, Charles A.
Abstract: The Naval Undersea Warfare Center Division Newport (NUWCDIVNPT) and Georgia Tech Research Institute (GTRI) completed a successful at-sea exercise with autonomous UAS and UUV systems demonstrating communication and collaboration. The exercise represented for the first time the use of standard protocols and formats that effectively support cross-domain unmanned system operations. Four man-portable Iver2 UUVs operating in coordinated missions autonomously collected environmental data, which was compressed in-stride, re-formatted, and exfiltrated via UAS relay for display and tactical decision making. Two UAS with autonomous flight take-off and mission execution were sequenced to serve as ISR platforms and to support communications as RF relays for the UUVs performing Intelligence Preparation of the Environment missions. Two Command and Control nodes ashore provided unmanned system tasking and re-tasking, and they served to host and display both geo-positional data and status for UAS and UUV vehicles during the operational scenarios run during the exercise. The SAE Joint Architecture for Unmanned Systems (JAUS) standards were used for all message traffic between shore-based C2 nodes, UAS, and UUVs active in the exercise area. Development for this project highlighted both the strengths and shortfalls of JAUS and captured the requirements for moving forward in effective cross-domain communications that support distributed, agile C2 nodes to meet evolving CONOPS for growing unmanned system presence and mission roles. The JAUS architecture was introduced to the NUWC and GTRI unmanned systems though an instantiation of the Mission Oriented Operating Suite (MOOS) autonomy framework on secondary CPUs integrated into the Iver2 UUVs and the GTRI UAS. This work represents a critical step in communications for networking of heterogeneous unmanned systems and establishes a solid platform for alignment of development and ongoing programs.